Islamic Qur’anic and Hadith Literacy: Thematic Tafsir of Iqra’, Qalam, ‘Ilm and Reading Culture - Rahman Rahman; Khairuddin Khairuddin; Ahmad Ghozali; Perdamaian Perdamaian; Suardi Suardi; Wasalmi Wasalmi (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2026)
Literacy has become one of the fundamental pillars of human civilization and a key element in the development of knowledge-based societies. In the Islamic tradition, literacy is not only understood as the ability to read and write but also as a comprehensive process of acquiring, developing, and disseminating knowledge. This study examines the concept of literacy in the Qur’an and Hadith through a thematic tafsir (tafsīr mawdū’ī) approach, focusing on the concepts of Iqra’ (read), Qalam (pen), and ‘Ilm (knowledge). The research employs a qualitative library research method by analyzing Qur’anic verses, prophetic traditions, and classical and contemporary exegetical literature. The findings show that the command of Iqra’ in the first revelation emphasizes intellectual engagement and critical reading, while Qalam symbolizes documentation, knowledge transmission, and the preservation of civilization. Moreover, ‘Ilm demonstrates that literacy in Islam includes cognitive, ethical, and spiritual dimensions. Hadith literature reinforces these principles through encouragement to seek knowledge, teach others, and document beneficial information. The study concludes that the Qur’an and Hadith establish a holistic literacy framework integrating reading, writing, reflection, and knowledge dissemination. In the contemporary context, these teachings remain relevant in strengthening literacy culture, fostering critical thinking, and promoting lifelong learning amid digital challenges. Therefore, Islamic literacy values serve as a moral and intellectual foundation for an enlightened, knowledge-oriented society.